The Somatechnologies of Canada's Medical Assistance in Dying Law: LGBTQ Discourses on Suicide and the Injunction to Live. (September 2017) - Baril, Alexandre
Abstract : In June 2016, the Canadian government passed Bill C-14 on medical assistance in dying, allowing for medically assisted suicide when 'death has become reasonably foreseeable.' While available for ill or physically disabled people at the end-of-life, medically assisted suicide is denied in cases where people are perceived to have a mental disability and whose suffering is strictly emotional/psychological, such as suicidal people. I argue that this distinction results in constructing two classes of suicidal subjects by considering physically disabled or ill people as legitimate subjects who should receive assistance in dying and suicidal people as illegitimate subjects who must be kept alive through what I call the 'injunction to live' and 'somatechnologies of life'. Analysing discourses on suicide targeting lesbian, gay, bisexual, trans* and queer (LGBTQ) people in LGBTQ scholarship, I argue that, based on the silencing of suicidal subjects through the injunction to live, suicidal people constitute an oppressed group whose claims remain unintelligible within society, law, medical/psychiatric systems and LGBTQ scholarship. This article calls for listening to suicidal people's voices and developing an accountable response to their suffering and claims.